An evaluation of some alkaloids of Papaver somniferum - Gürkan, Elçin (Marmara Pharmaceutical Journal, 1987)
This work covers up the comparison of the amounts ao the morphine, codeine, thebaine and morphinN-oxides in dry capsules-dry stems and wet capsule-wet stems of P.somniferum L. collected in Turkey.